The use of adaptive physical culture in the comprehensive rehabilitation of children with cerebral palsy - Yatsun S.M. ,; Volodin A.V. ,; Luneva N.V. ,; Semizorov E.A. , (Theory and Practice of Physical Culture, 2025)
Objective of the study is to identify the effectiveness of a comprehensive rehabilitation program for primary school children with cerebral palsy using adaptive physical education (APE) tools. Methods and structure of the study.Aspart of an experimentconductedatKurskboardingschoolNo.3,sixteenchildren(equallyboysandgirls)aged7-9yearswith a diagnosis of cerebral palsy(spasticdiplegia,GMFCSlevel1) were engagedin a specialadaptivephysicaleducationprogram.Thisprogramconsistedofthreeblocks: general development exercises, fitballexercises and water exercises,andwasaimedatcorrectingmotordisorders,developingcoordinationandformingcorrectposture. Results and conclusions. The experiment, which included goniometry and pedagogical testing, demonstrated the positive effect of the developed program of comprehensive rehabilitation with AFC on the motor functions of the lower extremities. The subjects showed an increase in the angle of flexion in the hip joints and dorsal flexion in the ankle joint. In addition, the indicators of balance and performance of dynamic exercises (squats and walking) improved. The study confirms the effectiveness and expediency of using this AFC program in the comprehensive rehabilitation of primary school students with cerebral palsy, which is reflected in an increase in the time of balance, the number of steps and squats, as well as the amplitude of movements in the joints.